GAMBARAN TENTANG PERSEPSI MASYARAKAT TERHADAP PERTOLONGAN PERTAMA PADA KECELAKAAN LALU LINTASDI DESA SAWO KECAMATAN JETIS KABUPATENMOJOKERTO - Triwibowo, Heri; Eka Setyawan, Ogiek (JURNAL KEPERAWATAN BINA SEHAT, 2015)
In Indonesia just a few people who know the proper handling of emergency cases to prarumah pain. As the community also still believe the myths related to the handling of such cases. This is the one who caused the accident victim mortality prior to the hospital to remain high. The purpose of the research is to know the description of the public perception of first aid on a traffic accident in the SawoJetis, Mojokerto. The design of this research is deksriptif. Research of variable areperception of people towards first aid at traffic accidents. The population are all of citizens at sawoJetis, Mojokerto as many as 1,102 KK. The samples were taken with purposive sampling technique as much as 43 KK. Data collected by questionnaire instrument and processed in coding, editing, scoring, and the tabulating later presented in the form of a frequency distribution table. The results showed that most of the perceptions of the respondents have a negative perception of first aid at accidents by as much as 25 respondents (58.1 percent). The public perception of first aid at the accident in SawoJetis, Mojokerto has a negative perception of the majority. This happens because the factors are influenced by experiences that are based on age, education.so health workers are expected to further improve services especially about giving health education to the public about the conduct of first aid at an accident so that the community can take action with more appropriate aid.Key Words : Perception, First Aid on Traffic Accident